2016
DOI: 10.1002/ppap.201500204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electrical Discharge Plasma in a Gas‐Liquid Flow Reactor Using Optical Emission Spectroscopy and the Formation of Hydrogen Peroxide

Abstract: Optical emission spectroscopy was used to characterize an electrical discharge plasma reactor with a liquid H 2 O film contacting different carrier gases. The plasma gas temperatures for Ar, He, and 1% N 2 in Ar were 1000-1200 K and did not vary significantly with liquid flow rate. Increasing solution conductivity by adding KCl to deionized water in the Ar case lowered the temperature by 13%, increased the discharge power and lowered the H 2 O 2 formation rates. The temperature was highest in the case of air (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…This window contains the (0,0) band of the N 2 (C 3 Π u → B 3 Π g ) transition. The rotational temperature obtained from this band is believed to reliably reflect the translational temperature of gas [19,29,30,31].…”
Section: Experimental Setup and Data Acquisitionmentioning
confidence: 98%
“…This window contains the (0,0) band of the N 2 (C 3 Π u → B 3 Π g ) transition. The rotational temperature obtained from this band is believed to reliably reflect the translational temperature of gas [19,29,30,31].…”
Section: Experimental Setup and Data Acquisitionmentioning
confidence: 98%
“…Temperature measurements carried out by Hsieh et al indicated the significant effect of O 2 in the mixture, which increased the plasma temperature. The authors also pointed out that higher power can be related to the change in UV radiation and affecting H 2 O 2 production [32]. Results obtained by Wang et al [33] indicate that NO x production depends mainly on vibrational excitation of N 2 and to a lesser extent on the thermal process.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, other less probable pathways such as OH + H 2 O *  → H 2 O 2  + H2728 are also possible. In fact, there exist many reports on the H 2 O 2 formation by discharge plasma operated over and inside aqueous solutions272829303132333435. However, the determining factors which influence the H 2 O 2 production from the plasma-water interactions remain unclear.…”
mentioning
confidence: 99%